Tourism Potential of MICE (Meetings, Incentives, Conferences, and Exhibitions) with SWOT Analysis in Asahan Regency in North Sumatra Province - Muhammad Halfi Indra Syahputra (Budapest International Research and Critics University, 2022)
The aim of this study is to investigate Asahan Regency's strengths, weaknesses, opportunities, and threats related to MICE tourism management. Using a SWOT (Strength, Weakness, Opportunities, Threats) analysis, the used method is descriptive qualitative. As a result of the research, it can be observed that Asahan Regency remains in S< W and O≥T, necessitating internal consolidation; nevertheless, the O≥T has development potential. By addressing deficiencies and bolstering strengths in detail, the fundamental weaknesses are the absence of a tourism information center, the absence of branding or a brand name, the absence of business investors, the absence of promotions for adequate lodging, and the presence of a lot of road access that has not been optimized for cross-road or infrastructure that has not been fully exploited.